The Structural Semiotics of Joseph (AS) in the Holy Quran - Ali bagher Taheriniya; Masoumeh Shabestari; Mohammad ali Ameri (دراسات في اللغة العربيّة وآدابها)
The literary semiology of personality is a type of semiotic study which provides a deep and accurate knowledge and insight into personality and can be undertaken from various dimensions and angles. The Holy Quran, as a most significant literary text, is full of linguistic signs on set of which being the various personalities that are directly referred to in the Quran. Saint Joseph (Yusuf) (AS) is one of the most important figures in the Quran. Therefore, his semiotic study can lead to understandings about his character and the motivations and reasons for his personality traits. The present article is based on the personality semiology of the French semiologist Philip Hamon. This article studies Joseph’s personality in Quran from the perspective of the signifier (names, syntactic features, pronouns and rhetorical dimensions) and the signified (descriptive adjectives, speech, and actions). This article show that names, honorifics, and the descriptions for Joseph are in compliance with the function of his story. Through semiology and interpretation, the article gives a deeper insight about Joesph’s personality can help understand the nuances of the related Quranic meanings.